PENGGUNAAN MEDIA MONTASE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPA - Mira Azizah; Rofian Rofian; Inggi Rosiamali Sholikhah (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
USE OF MONTASE MEDIA TO IMPROVE STUDENTS' CRITICAL THINKING ABILITY IN NATURAL SCIENCE SUBJECTSThe background of this research was due to the low level of students' critical thinking skills in science subjects and the low utilization of montage media during learning. The purpose of this study was to determine the use of montage media to improve students' critical thinking skills in science subjects. This type of research is an experiment using a quantitative approach with the One Group pretest-posttest design. The population in this study were students of class V SD Negeri 02 Tanjungsari Pemalang, totaling 24 students. The sample in this study were students of class V SD Negeri 02 Tanjungsari Pemalang, totaling 24 students. The data were collected using a critical thinking skill description test. Data were analyzed by statistical analysis, gain score test, and t test. Based on the results of the analysis, it shows that there is an increase in students' critical thinking skills in science subjects using montage media with the results obtained at tcount = 9.64581 t table = 2.06866. Students' critical thinking skills have increased with the n gain test obtained by 16 students (66.7%) in the Medium category. The results of this study concluded that the use of montage media could improve students' critical thinking skills in science subjects.